The Institutionalization of Inter-Municipal Arrangements in Europe: Findings from the Unusual Suspects - Paweł Swianiewicz; Filipe Teles (Transylvanian Review of Administrative Sciences, 2019)
Research on Inter-Municipal Cooperation (IMC) in Europe suffers from a deficit of international comparative studies. This article presents an in-depth analysis of the level of institutionalization of IMC arrangements, claiming its relevance for future research and suggesting a set of post-typological dimensions needed for its characterization. It ends with a recommendation of new research agendas. In addition to bringing up-to date information, it aims at contributing with new knowledge by including countries not involved in previous comparative research and new ‘after crisis’ data. The research methodology also allowed the analysis of individual institutions.